Efficiency of the state youth policy in the Republic of Khakassia - T B Shigolakova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
The article considers the efficiency of the state youth policy in the Republic of Khakassia in 2010-2013 focusing on the changes in the number of specialists in the field of youth policies, and representatives of public associations that completed the advanced training and retraining programs; on the percentage of young people aged 14 to 30 involved in volunteer activities and projects for promoting ideas of patriotism, civil responsibility and tolerance, as well as in business activities and student groups; on the number of projects and programs submitted for the grant competition of the Government of the Republic of Khakassia in the field of youth policies; and on the measures to support talented young people, etc. The author identifies key indicators to assess the situation in the different spheres of the youth policy in terms of its focus and priorities. For instance, to evaluate the efficiency of measures to combat drug abuse and illegal drug trafficking we are to compare the annual numbers of young people involved in activities to prevent drug abuse, and to consider the dynamics of decrease of drug trafficking; to evaluate the efficiency of crime prevention, and maintaining security and public order we are to consider the rates of crimes committed by minors and young people; to assess the development of innovative, scientific and applied activities we are to check the dynamics of the number of young researchers involved in such activities, as well as the number of scientific schools in Khakassia, etc.